Impaired clinical, biological, and cytokine patterns in HIV-1 exposed uninfected newborns in Yaoundé: A comparative study of neonatal immune vulnerability - Sabine A. Touangnou-Chamda; Palmer M. Netongo; Jacky Njiki Bikoï; Véronique S. Mboua Batoum; Donatien S. Mbaga; Carole S. Sake; Marie-Christine M. Nzuno; Chris M. Nana Mbianda; Maurice Boda; Sara H. Riwom Essama (African Journal of Laboratory Medicine, 2026)
Background: Immune dysregulation is hypothesised to underpin the heightened susceptibility of HIV-1-exposed uninfected (HEU) infants to morbidity and mortality, which occurs at a rate three times higher than that of HIV-1-unexposed uninfected (HUU) controls. However, robust evidence substantiating this hypothesis and advocating targeted interventions remains scarce in Cameroon. Objective: To examine how maternal HIV-1 infection influences the immune response of HEU neonates in Yaoundé. Methods: A comparative cross-sectional study was conducted in 280 mother–child pairs at birth in Yaoundé. Clinical parameters were assessed, while umbilical cord blood samples from both HEU and HUU newborns were analysed for comprehensive immunophenotyping and quantification of 12 pro-inflammatory and anti-inflammatory cytokines. Results: Significant differences were observed between HEU (representing 100% of exposed newborns tested) and HUU newborns. Notably, 1/54 (1.85%) of HEU newborns exhibited a lower Appearance, Pulse, Grimace, Activity, Respiration score at 1 min (p = 0.01); HEU expressed severe leucocytosis (p = 0.008) and neutropaenia (p = 0.01). As well, dysregulated cytokine production was observed, with significantly elevated levels of pro-inflammatory cytokines Interleukin-6 (IL-6) (p = 0.003) and Interleukin-1 beta (IL-1β) (p = 0.004), as well as decreased levels of anti-inflammatory cytokine Transforming Growth Factor beta 1 (p = 0.024). Strong negative correlations were further demonstrated between monocytes and pro-inflammatory cytokines IL-1β (r = −0.74), Interleukin-5 (r = −0.75), and IL-6 (r = −0.75), (p < 0.001). Conclusion: Maternal HIV-1 infection is associated with impaired outcomes in HEU newborns, highlighted by immune dysregulation in an early pro-inflammatory environment. These findings underscore the heightened vulnerability of HEU neonates and elucidates the underlying factors contributing to their subsequent health challenges. What this study adds: It provides initial information on pertinent but not yet described pro-inflammatory cytokines impairment in Cameroonian HEU newborns. Unlike previous research that has focused on their KIR-21 gene expression and responsiveness to measles vaccine, this study introduces their immunological responses through their umbilical cord blood analysis, a previously unexamined specimen.